Synthesis and evaluation of 3-alkynyl-5-aryl-7-aza-indoles as broad-spectrum antiviral agents - Martinez-Gualda, Belén; Graus, Mirthe; Camps, Anita; Vanhulle, Emiel; Saul, Sirle; Azari, Siavash; Nhu Tran, Do Hoang; Vangeel, Laura; Chiu, Winston; Neyts, Johan; Schols, Dominique; Einav, Shirit; et al. (Frontiers in Chemistry, 2022)
RNA viral infections, including those caused by respiratory syncytial virus (RSV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and Venezuelan Equine encephalitis virus (VEEV), pose a major global health challenge. Here, we report the synthesis and screening of a series of pyrrolo[2,3-b]pyridines targeting RSV, SARS-CoV-2 and/or VEEV. From this campaign, a series of lead compounds was generated that demonstrated antiviral activity in the low single-digit micromolar range against the various viruses and did not show cytotoxicity. These findings highlight the potential of 3-alkynyl-5-aryl-7-aza-indoles as a promising chemotype for the development of broad-spectrum antiviral agents.